PENGEMBANGAN KETERAMPILAN MEMBANTU DIRI SENDIRI PADA ANAK PANTI ASUHAN USIA 4-5 TAHUN - Ade Dwi Utami Ristiaji Yunitami (Direktorat Pembinaan Guru dan Tenaga Kependidikan Pendidikan Anak Usia Dini Kementerian Pendidikan dan Kebudayaan bekerjasama dengan Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2014)
This study aims to investigate the case of the self-help skills in the orphanage children aged 4-5 years old. The study took place at Yayasan Arrohmaniyah Panti Asuhan Yatim Piatu Anni’mah, Cakung, East Jakarta. The method used in this research is a case study. Data collection techniques used was observation, interview, and documentation. In the data analysis, this study using Miles and Huberman. Activities undertaken in the analysis of data such as data reduction, data display and conclusion drawing / verification. Orphanage children who are in the age range 4-5 years to be subjects in this study. In the observations made during the study obtained data is that children aged 4-5 years living in orphanages have had self-help skills. Self-help skills possessed these children appear in fulfilling the needs and tasks that can be done without the intervention of an adult. Field data indicate that the opportunity to do the task and given caregiver needs. Attempts are made in the process of growing self-help skills provided caregivers on Yayasan Arrohmaniyah Panti Asuhan Yatim Piatu Anni’mah.